2003
DOI: 10.1136/jnnp.74.8.1060
|View full text |Cite
|
Sign up to set email alerts
|

Social deprivation and adult head injury: a national study

Abstract: Objectives: To establish the association between measures of social deprivation, mechanisms of injury, patterns of care, and outcome following closed head injury. Methods: All Scottish adult A&E attendees with closed head injury (AIS Head >3) between July 1996 and December 2000 were studied. Results: Trauma was more common in individuals from more deprived areas. Within the trauma population head injury was relatively more common in patients from deprived areas; these individuals were more likely to sustain an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 19 publications
2
26
1
1
Order By: Relevance
“…This finding supports Dunn et al who reported that head injured patients in the 'more deprived' group were more likely to sustain their injury as a result of assault. 6 They also reported that the patients in the less-deprived group were more likely to be in a road traffic accident or to have fallen from a height; however, the results of this study found no significant difference in any other injury mechanism. This may be due to the different injured body part under investigation.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…This finding supports Dunn et al who reported that head injured patients in the 'more deprived' group were more likely to sustain their injury as a result of assault. 6 They also reported that the patients in the less-deprived group were more likely to be in a road traffic accident or to have fallen from a height; however, the results of this study found no significant difference in any other injury mechanism. This may be due to the different injured body part under investigation.…”
Section: Discussioncontrasting
confidence: 56%
“…This result does not support the results of Dunn et al who reported that headinjured trauma patients from a more deprived area had shorter median length of stay than the headinjured patients from a less-deprived area; however, this may again reflect the difference in body part injured. 6 It could be suggested that the increased incidence of prolonged length in the 'more deprived' group of patients is due to a number of factors including higher rates of alcoholism and smoking, but further research in this area would be needed to draw firm conclusions. As a result of the risk of prolonged length of stay in the more deprived isolated blunt chest wall trauma patient, the clinician managing the patient should consider the patient's social status when planning for hospital discharge.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Carstairs score is a -score based on overcrowding, male unemployment, social class, and car ownership. It has been extensively used to examine social deprivation in orthopaedic surgery [7,8,12] and other branches of medicine [9,13]. The Carstairs score can be used to divide the population of Scotland into five equal quintiles, with Quintile 1 (Q1) being the most affluent and Quintile 5 (Q5) being the most deprived.…”
Section: Methodsmentioning
confidence: 99%